Frequency and variability of dental morphology of temporal and permanent molars in a group of Caucasoid mestizos from Popayán (Cauca, Colombia) - Perez, Camila; Sanchez, Claudia; Moreno, Sandra; Moreno, Freddy (Revista Estomatología, 2017)
Objective: To determine the frequency and variability of dental morphology in temporary and permanent molars of a group of Caucasoid mestizos from Popayán (Cauca, Colombia), in order to generate new group markers that allow comparing the different Colombian and world populations from nine coronal dental morphological features (NMDT). Materials and methods: quantitative, descriptive, cross-sectional study that determined the frequency and variability of nine NMDT (Carabelli trait, hypocone reduction, metaconule, cusp pattern, cusp number, defleckting wrinkle, protostilyd, cusp 6 and cusp 7) using the ASUDAS methodology In 101 self-described individuals as Caucasoid mestizos (59 females and 42 males), aged between 10 and 17 years. Results: Significant reduction frequencies of the hypoconus (89.9%), cusp pattern in Y (81.6%) and number of cusps (92.7%) were identified; And low frequencies of metacele (0.2%), protostilyd (0.6%) and cusp 6 (0.2%). No sexual dimorphism and bilateral asymmetry were found in the NMDT studied. Conclusions: The sample studied is characterized by a dental morphology characteristic of Colombian mestizo populations that are included in the Caucasoid dental complex (Carabelli cusp, reduction of the hipocono and number of cusps). However, due to the ethnohistorical processes of the geographic region where they are located, they are influenced by indigenous groups (cuspid expression) included in the mongoloid dental complex.